External Debt In Indonesia’s Economic Growth: Role Macroeconomic Performance - amilusholihah; Waspada, Ikaputera (JIES : Journal of Islamic Economics Studies, 2024)
The aim of this study is to analyze the impact of Gross Domestic Product (GDP), exports, foreign exchange reserves, and exchange rates on Indonesia's external debt. A quantitative approach was employed using multiple linear regression analysis techniques with Ordinary Least Squares (OLS) methodology, conducted through SPSS software version 24. Annual time series data for 26 years, from 1997 to 2022, were obtained from the World Bank and Bank Indonesia (BI). The study results indicate that simultaneously the independent variables GDP, exports, foreign exchange reserves and the exchange rate have a significant effect on foreign debt. Then, partially with a significance level of five percent, the GDP and exchange rate variables have a positive and significant effect on Indonesia's external debt. Meanwhile, exports and foreign exchange reserves have a negative and significant effect on Indonesia's external debt. These results suggest that external debt continues to be a significant policy tool for promoting Indonesia's economic development and growth. Therefore, it is recommended that the government concentrate on macroeconomic strategies, such as increasing exports of high-value commodities, ensuring exchange rate stability, and optimizing external debt for investment in productive sectors, to promote economic expansion.